2015
DOI: 10.1016/j.celrep.2015.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Age-Related Infertility under Environmental Light-Dark Cycles Adjusted to the Intrinsic Circadian Period

Abstract: Female reproductive function changes during aging with the estrous cycle becoming more irregular during the transition to menopause. We found that intermittent shifts of the light-dark cycle disrupted regularity of estrous cycles in middle-aged female mice, whose estrous cycles were regular under unperturbed 24-hr light-dark cycles. Although female mice deficient in Cry1 or Cry2, the core components of the molecular circadian clock, exhibited regular estrous cycles during youth, they showed accelerated senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
1
36
1
Order By: Relevance
“…However, findings that a point mutation of the clock gene Clock disrupts the secretion of sex hormones and the normal estrous cycle in mice strongly indicate that night-work-induced circadian misalignment may have a negative impact on reproductive function in women (Miller et al 2004). Furthermore, a very recent study reported that a difference in period between internal (circadian) and external (environmental) rhythms causes irregular estrous cycles: although female mice lacking the clock gene Cryp-tochrome1 or Cryptochrome2 have a different intrinsic circadian period to wild-type mice and therefore show irregular estrous cycles in a regular 24-h lightdark period, the estrous cycle of Cry-deficient mice is restored when the period length of environmental light-dark cycles is adjusted to the same period as the intrinsic circadian period (Takasu et al 2015). Adding more direct evidence for the negative impact of night work on the menstrual cycle, we here report that the repetitive reversal of light-dark (LD) cycles triggers irregular estrous cycles in mice and that the negative impact remains even more than four weeks after mice are returned to a regular LD cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings that a point mutation of the clock gene Clock disrupts the secretion of sex hormones and the normal estrous cycle in mice strongly indicate that night-work-induced circadian misalignment may have a negative impact on reproductive function in women (Miller et al 2004). Furthermore, a very recent study reported that a difference in period between internal (circadian) and external (environmental) rhythms causes irregular estrous cycles: although female mice lacking the clock gene Cryp-tochrome1 or Cryptochrome2 have a different intrinsic circadian period to wild-type mice and therefore show irregular estrous cycles in a regular 24-h lightdark period, the estrous cycle of Cry-deficient mice is restored when the period length of environmental light-dark cycles is adjusted to the same period as the intrinsic circadian period (Takasu et al 2015). Adding more direct evidence for the negative impact of night work on the menstrual cycle, we here report that the repetitive reversal of light-dark (LD) cycles triggers irregular estrous cycles in mice and that the negative impact remains even more than four weeks after mice are returned to a regular LD cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Because these abnormal circadian characteristics made it difficult for these mice to adapt regular LD cycles, arterial plaque formation may be differently affected by chronic forced adaptation to the environment compared to the free-running condition (DD). As another example that the difference between internal and external rhythmicity causes homeostatic dysfunction, a very recent study using Cry KO mice reported that the difference between internal and external period lengths causes irregular estrous cycles in mice (Takasu et al, 2015). However, to fully resolve this issue, an experiment such as forced desynchrony or an LD schedule which exceeds the limits of circadian entrainment is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian clock genes (period [Per]1, Per2, cryptochrome [Cry]1, Cry2, Clock, and Bmal1) in SCN give rise to a rhythm with a period of approximately 24 hours by means of transcription-translation feedback loops. [6][7][8][9] Importantly, the circadian clock gene network plays a significant role in mammalian energy balance. Clock mutant mice have a greatly attenuated diurnal feeding rhythm, are hyperphagic and obese, and develop a metabolic syndrome of hyperlipidemia, hyperglycemia, and hypoinsulinemia.…”
mentioning
confidence: 99%